A phase 3, randomized study of ofatumumab combined with bendamustine in rituximab‐refractory iNHL (COMPLEMENT A + B study). (10th May 2021) - Rummel, Mathias J.; Janssens, Ann; MacDonald, David; Keating, Mary‐Margaret; Zaucha, Jan M.; Davis, Jaclyn; Lasher, Janet; Babanrao Pisal, Chaitali; Izquierdo, Miguel; Friedberg, Jonathan W.
Summary: The standard of care for indolent non‐Hodgkin lymphoma (iNHL) is rituximab, an anti‐CD20 antibody, with/without chemotherapy. However, multiple relapses are common in these patients. This phase 3, randomized study compared outcomes of a combination of ofatumumab (a second‐generation anti‐CD20 antibody) and bendamustine, with bendamustine alone in patients unresponsive to prior rituximab‐based treatment. Overall, 346 patients were randomized to receive either the combination or bendamustine alone. Bendamustine was given for ≤8 cycles and ofatumumab for ≤12 cycles. The primary end‐point was progression‐free survival (PFS) after 215 protocol‐defined events assessed by independent review committee (IRC). Median IRC‐assessed PFS was 16·7 and 13·8 months in the combination and monotherapy arms respectively [hazard ratio (HR) = 0·82; P  = 0·1390]. Median overall survival (OS) was 58·2 and 51·8 months in the combination and monotherapy arms respectively (HR = 0·89, P  = 0·4968). The safety profile was consistent with previous reports. Overall, 73% and 80% of patients in the combination and monotherapy arms, respectively, experienced a ≥grade 3 adverse event. The study did not meet its primary end‐point. No significant improvement in PFS and OS was seen with the combination of ofatumumab and bendamustine as compared with bendamustine alone in rituximab‐refractory iNHL (NCT01077518).